Effects of the use of ICT on learning assessment: Impact of an electronic voting system - López Rodríguez, Mª Isabel; Barac, Maja (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
We used a gamification tool, an electronic voting system, in a university-level subject. We analyzed whether the use of this tool in the continuous assessment activities had an impact on the teaching-learning process, specifically, on the results of the final exam. To this end, we collected data on student characteristics potentially influencing academic performance, which we studied by applying descriptive and inferential data analysis techniques. The result shows that students can increase their score by almost 2 points, depending on their correct answer ratio with the electronic voting system.